Keberkesanan Program Skim Latihan Graduan bagi Mengurangkan Kadar Pengangguran Dalam Kalangan Siswazah - Abdul Rauf, Siti Hajar; Abdul Rauf, Maimunah (2012)
Unemployment among graduates has been an often discussed issue over the last few years. The establishment of more institutions of Higher Learning by government and private sector have an impact on development and changes in the country. These developments have led to an increase in the amount of labor, thus increasing unemployment among graduates. Therefore, a study was done to see to what extent the Graduate Training Scheme Program (SLG) is effective in improving skills and employability to help equip graduates with specific skills needed by employers. This study was conducted using quantitative methods. A total of 100 sets of questionnaires were distributed to all respondents across Terengganu. In addition, in-depth interviews were also carried out on six of the informants, comprising employers in training trainers. The results show there was a minimum relationship between education and the suitability of a position they held at the end of the SLG programme where the value of correlations equals to (r =.306, p >.05). Meanwhile, there is a very strong relationship between the skills acquired and the ability of graduates to obtain employment upon completion of training which is (R = .911), this shows that the dependent variable, skills have an influence on a trainee to be admitted to work. At the same time, the interviews show that distinctive value-added assets for employment are the relationship with the industry, the ability of graduates to work individually or by group, ability to finish tasks within a given time, experience, skilled and having interpersonal skills.